Biofictions Race, Genetics and the Contemporary Novel - Gill, Josie (Bloomsbury Academic, 2020)
In this important interdisciplinary study, Josie Gill explores the ways in which the contemporary novel has drawn on and helped shape debates about race and identity in 21st century genetic science. Reading works by leading contemporary writers such as Zadie Smith, Alex Haley, Octavia Butler and Salman Rushdie, Biofictions demonstrates how ideas of race are produced from intersecting genetic and fictional narratives which together create stories about racism, ancestry and kinship.